Isolated Cerebellar Stroke Masquerades as Depression - Othman, Zahiruddin; Misron, Siti Nor Fadhlina; Azizan, Mohammad Nabhan Khalil (Japan International Cultural Exchange Foundation, 2018)
Objective: There are numerous reports on neurological conditions masquerading as psychiatric disorders. However, cerebellar stroke is not established as one of it. The 2 case reports will highlight that this masquerade is possible and the physician's high index of suspicion is the key to accurate diagnosis. Results: The case reports illustrated how a cerebellar stroke could be misdiagnosed as a depression due to its presenting symptoms of vertigo. The rarity of cerebellar stroke itself already posed a challenge for the physician to detect it but the mimicking of depression was the ultimate obstacle. Conclusion: The acute onset strongly suggests an organic cause. It is important to ascertain depression through depressive mood, and not by behavioral changes alone. Correct diagnosis of cerebellar stroke is of paramount importance so that early intervention can be delivered to the patient.